A NOTE ON OPTIMAL DEBT REDUCTION POLICIES. (21st October 2020) - la Torre, Davide; Marsiglio, Simone
Abstract : We analyze the optimal debt reduction problem in an uncertainty context. The social planner has a finite horizon and seeks to minimize the social costs associated with debt repayment by taking into account not only the short-run costs of the policy, but also the long-run costs associated with the outstanding level of debt. We characterize the optimal policy and the dynamics of the debt-to-GDP ratio, showing that it will decrease over time if economic policy is effective enough. We characterize how the evolution of the debt-to-GDP ratio depends on the main parameters and we present a simple calibration based on Greek data to illustrate the implications of our analysis in real-world setups.